Halide‐Substituted Phosphacyclohexadienyl Iron Complexes: Covalent Structures vs. Ion Pairs. Issue 11 (8th March 2019) - Hoidn, Christian M.; Leitl, Julia; Ziegler, Christoph G. P.; Shenderovich, Ilya G.; Wolf, Robert
Abstract: Invited for the cover of this issue is the group of Robert Wolf from the University of Regensburg, Germany. The cover image shows the structure of the first transition metal complexes bearing π‐coordinated λ 3 ‐halophosphacyclohexadienyl ligands, featuring polarized P–halogen bonds. Abstract : Phosphinines have unique reactivity and versatile coordination behavior … Read more about the story behind the cover in the Cover Profile and about the research itself in the Full Paper by R. Wolf et al.